Mối quan hệ giữa thị trường chứng khoán và thị trường bất động sản: Trường hợp tại Thành phố Hồ Chí Minh - Phan Thi Bich , Nguyet; Pham Duong Phuong, Thao (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
This study inspects the relationship between the stock market and real estate market in Vietnam, particularly with the case of Ho Chi Minh City from Q1/2009 through Q3/2014. Using a survey of expert opinions, we find that several macro factors including GDP, interest rate, inflation, fiscal policy, monetary policy, and securities regulations, international capital flows and money market have effects on both the stock and real estate markets, which, in turn, do have mutual interactions. Furthermore, it is suggested by the survey results that among the determinants, policy on foreign investment control has the most powerful impact on capital movements between the two markets. The results of TECM analysis of property price index and VN-Index reveal a two-way relation between the two markets, which are positively related in the long run.